DISCUSSING THE ADOLESCENCE SERIES – BETWEEN IGNORANCE AND THE REGULATION OF THE PUBLIC SQUARE - Zucoloto, Karla Aparecida; da Silva, Pedro Henrique Zucoloto (Seven Editora, 2025)
This study aims to analyze the adolescent phenomenon under the studies of the pedagogue, psychology, and legislation from the series Adolescence, of a subscription streaming service. The series consists of 4 episodes that deal with a crime committed by a 13-year-old boy from the point of view of the State, the school, forensic psychology, and the family, It was analyzed in its constitutive episodes to discuss human development in adolescence and the need for regulation of social networks. The objective of this study was to analyze the behavior of adolescents in the hyperconnected world and the increase in cases of violence among young people and adolescents to try to delimit the role of different adults in different social contexts. The data on the significant increase in violence among adolescents and young people point to the lack of control over social life, due to the early exposure of this group to different social media. Making us rethink the role of the State, the school, parents, and specialists in the role of taking care of our children and young people.